Ecologia de peixes de riachos da bacia do rio Machado, RO: padrões, processos e conservação - Pérez-Mayorga, María Angélica [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this thesis, the effects of local, landscape and spatial variables on composition, abundance, functional traits and phylogeny of stream ichthyocenoses were analyzed. Based on fish species, environmental and spatial datasets from 52 (2012 samples) and 75 (2011 and 2012 samples) stream reaches located in the Machado River basin, in the state of Rondônia, three chapters were organized. The highlight of the chapter one was the ecological patterns of all species of entire metacommunity and fish assemblages according to their degree of habitat specialization (habitat generalists and habitat specialists). The three cenoses were environmentally structured, suggesting that the niche-based processes explain their structure. In the chapter two, the ecological processes that probably explain the obtained patterns were explored more deeply. Both functional and phylogenetic clustering was confirmed. Environmental variables, such as the proportion of ultisol in the microbasin and of grasses and bared soil in the riparian buffer, structure the assemblages that are associated with degraded streams (DS). On the other hand, the proportion of forest and of oxisoil in the microbasin; coarse litter, shrubs and trees in the stream riparian buffer, structure the assemblages that are associated with the preserved streams (PS). The environment also influences through environmental filter mechanisms, the consumption of algae and the nektonic position in the water column in DS, whereas influences the consumption of invertebrates debris and the nektobenthic position in the water column in PS. The DS and PS position is coincident with the different land uses. DS are concentrated in the central portion of the basin, where the soil is covered by pastures, and PS are in the extremes of the basin, where there are greater proportions of forests. Most species of Siluriformes and of Characidae are associated with DS, on the other hand, Gymnotiformes, some species of ...

Na presente Tese, foram analisados os efeitos de variáveis locais, de paisagem e espaciais sobre a composição, abundância, traços funcionais e filogenia das ictiocenoses de riachos. Foram organizados três capítulos a partir da coleta da ictiofauna e dos dados ambientais e espaciais em 52 (coletas de 2012) e 75 (coletas de 2011 e 2012) trechos de riachos localizados ao longo da bacia do rio Machado, no estado de Rondônia. O foco do capítulo 1 foram os padrões ecológicos de todas as espécies da metacomunidade e das assembleias de peixes segundo a especialização do hábitat (hábitat especialistas e hábitat generalistas). As três cenoses foram estruturadas ambientalmente, sugerindo que são os processos baseados em nicho os que explicam a sua estrutura. No capítulo 2, exploramos mais a fundo os processos ecológicos que provavelmente explicam os padrões obtidos. Foi comprovado que há agrupamento nos traços funcionais e na filogenia. Variáveis ambientais, tais como a proporção de ultisolo na microbacia e gramíneas e barranco nu no buffer ripário, estruturam as assembleias associadas aos riachos degradados (RD). Por outro lado, a proporção de floresta e de oxisolo na microbacia; litter grosseiro, arbustos e árvores no buffer ripário do riacho estruturam as assembleias associadas aos riachos preservados (RP). O ambiente também influencia, através de mecanismos de filtros ambientais, o consumo de algas e a posição nectônica na coluna d'água nos RD, ao passo que influencia o consumo de restos de invertebrados e a posição nectobentônica na coluna d'água nos RP. A posição dos RD e RP é coincidente com os diferentes usos do solo, sendo os primeiros mais concentrados na porção central da bacia, onde o solo é usado para pastagens, e os RP nos extremos da bacia, onde há maiores proporções de florestas. A maioria das espécies das famílias Loricariidae e Characidae está associada aos RD, por outro lado,...
Keywords: Ecologia animal; Ictiologia - Rondônia; Peixe de agua doce - Habitat; Peixe - Filogenia; Educação ambiental; Animal ecology